The fall of Constantinople: Its musical remembrance in the 1950's - Windhager, Ákos (Études sur la Région Méditerranéenne, 2011)
In my article I present a comparative analysis of Manolis Kalomiris's opera the Constantine Palaeologus and Cemal Resid Rey's symphonic poem Fatih Sultan Mehmet from the point of view of national canons, political backgrounds and aesthetics. Both pieces deal with the last siege of Constantinople (1453), which ended in the victory of the Ottoman army. This historic turning point inspired very sophisticated, interpretative compositions on both of sides of the former frontline. In the epilogue of my article this horizon is widened by the Hungarian musical reading of this great historical event. In 1953 - 500 years after the siege - the contemporary artistic remembrance turned the fall of Constantinople into an important part of both national mythologies. These mythologies can demonstrate that Turkey belongs to Europe, and Europe is in debt to Greece. Both nations and even both states have problems with their respective political identities, with the acceptance of their near past and with their vulnerability to the new superpowers. Of course, the artistic pieces analysed below were composed not for political reasons, although their plots and receptions are understandable only with attention to the political background of their births.